The Impact of Hand Puppet Media on Speaking Skills in Children Aged 5-6 Years - Tri Septiani, Vesi; Murtopo, Ali; Dwi Sartika, Indah; Michael, Gurnick (Universitas Islam negeri Mahmud Yunus Batusangkar, 2024)
This study aims to identify the effect of using hand puppet media on the speaking skills of children aged 5-6 years. The research employed an experimental method with a One Group Pre-test Post-test design, involving 15 children as the sample. Data collection techniques included observation, tests, and documentation, while data analysis was conducted using normality tests, homogeneity tests, and hypothesis tests. Based on the findings, the hypothesis was accepted, indicating that the use of hand puppet media significantly enhances children's speaking skills. These results highlight the importance of utilizing creative and interactive learning media to support children's language development and encourage educators to adopt similar media in various learning contexts.